2001
DOI: 10.1186/1472-6882-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of lipid composition in aorta of guinea pigs by Curcuma domestica

Abstract: Background: A short-term study was carried out using guinea pigs to determine the effects of Curcuma domestica on lipid composition in the serum and aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Triglyceride content in aorta has been related to atherosclerosis in some studies [46] and has been demonstrated to be related to hypercholesterolemia. Similarly, in the present study, guinea pigs treated with RAPA had higher TG in plasma as well as in their aorta as compared to the control animals.…”
Section: Rapamycin and Liver And Aortamentioning
confidence: 98%
“…Triglyceride content in aorta has been related to atherosclerosis in some studies [46] and has been demonstrated to be related to hypercholesterolemia. Similarly, in the present study, guinea pigs treated with RAPA had higher TG in plasma as well as in their aorta as compared to the control animals.…”
Section: Rapamycin and Liver And Aortamentioning
confidence: 98%
“…Ezekwe and Obidoa 37 have reported that flavoniods, tannins and saponins may play some roles in the hypolipidaemic effect of some plants. The mechanism of the hypocholesterolaemic action of these plant leaves may be due to inhibition of the absorption of dietary cholesterol in the intestine or its production by the liver 38 or stimulation of the biliary secretion of cholesterol and cholesterol excretion in faeces 39 .…”
Section: Discussionmentioning
confidence: 99%
“…A 2 mm section of the aorta of each animal was soaked in 10% (v/v) formal saline solution for hematoxylin and eosin staining and another 2 mm section was placed in kriomatrix and kept at -20°C for frozen sections [21]. The remaining aorta was soaked in deionized water and homogenized for biochemical analyses.…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…The tissue samples were ultrasectioned (5-6 lm thickness), stained with hematoxylin and eosin and examined under a light microscope for observation of structural abnormality. Ultra-thin sections of the frozen aorta (8 lm thickness) were stained with Schultz stain [21,22] and examined for cholesterol deposits.…”
Section: Histopathological Studiesmentioning
confidence: 99%